Production risk and technical inefficiency of paddy farms in MADA granary area, Malaysia - Yahaya, Kaka (2016)
This study models technical inefficiency with production risk in inputs as two possible sources of the production variability that characterized Malaysian Paddy Production. Data from a total of 397 Paddy farms randomly sampled from MADA granary area were used for the analysis. The data for the study was sourced from the survey conducted for the period of 2014 farming season. The study employed a trans-log stochastic frontier production function model with flexible risk specification. The empirical estimates revealed that the mean output is positively influenced by seed, fertilizer, agrochemicals and labour. Fertilizer and agrochemicals are found to be riskreducing inputs, while seed and labour is revealed to be risk-increasing inputs. This by implication means that an average risk-averse producer is expected to use more of fertilizer and agrochemicals and less of seed and labour compared to risk-neutral producer in the study area. Several characteristics of farm operators such as age, education, marital status, household size, farming experience, extension visit, credit access, farm location, cultivation technology, MR219 and MR220CL2 seed variety, planting technology, broadcasting technology, agrochemicals use and harvesting technology were found to have significant effects on the technical inefficiency of paddy production in the study area. It was also revealed that extension visit, credit access, MR219 seed variety, MR220CL2 seed variety, method of broadcasting and harvesting technology significantly reduces the technical inefficiency of producers. The estimated technical efficiency indicates that the efficiency score is overstated when the production technology of the paddy farms is modelled without flexible risk component (87.1 percent) while it was found when estimated with risk component to be 83.6 percent. Profit efficiency of paddy farmers in the study area was also estimated. The model revealed that MADA farmers do not operate on the profit frontier. The average profit efficiency of 73.2 percent implies that, although farmers in the study area are relatively profit efficient, there are clear opportunities that exist for increasing their profit efficiency by almost an average of 27% through improving their technical and allocative efficiency.